(3OQGSI fXQjI JMdjdjI bjGSjIs - (3YHO GdbGOQ(B, (3bOGhjs; (3eMeO QGJhd(B, s ((3GdLRGFQ(B:s (3GdecJH GdLGeYj GdMOjK,s, 2017)
(3GdaUd GdGhd (B: (3GdHfGA GdfXQj dXGgQI Gdfeh GdScGfj eaGgje GdXGgQI GdScGfjI , GdfXQjGJ GdeaSQI ddfeh GdScGfj , eMOOGJ Gdfeh GdScGfj , NdGUI GdaUd GdaUd GdKGfj (B: (3eONd eaGej dXGgQI JRGjO GdfabGJ GdYGeI eGgjI GdfabGJ GdYGeI , XGgQI JRGjO GdfabGJ GdYGeI , VHW hJQTjO GdfabGJ GdYGeI , NdGUI GdaUd GdaUd GdKGdK (B: (3GdYdGbI GdfXQjI ddKfGFjI (B( (3JRGjO GdScGf (B- (3JRGjO GdfabGJ GdYGeI (B) (3eaghe hJWhQ GdSjGSGJ GdScGfjI, bfhGJ JCKjQ Gdfeh GdScGfj Ydi GdfabGJ GdYGeI , GdGKGQ GdGbJUGOjI GdcdjI ddfeh GdScGfj , NdGUI GdaUd GdaUd GdQGHY (B: (3JMdjd hbjGS CKQ Gdfeh GdScGfj Ydi GdfabGJ GdYGeI aj GdLRGFQ ddaJQI (B1990-2004 (3JWhQ XGgQI GdScGfjI hJRGjO GdfabGJ GdYGeI aj GdLRGFQ ,GdJaSjQ GdOjeZQGaj dJRGjO GdfabGJ GdYGeI aj GdLRGFQ , OQGSI bjGSjI dGKQ Gdfeh GdScGfj Ydi GdfabGJ GdYGeI aj GdLRGFQ ddaJQI (B1990-2004s
(3edGMb U(B. 275 (3HjHdjhZQGajG U(B.305 (3eUWdMGJ GdOQGSI (B232s
Keywords: (3GdLRGFQ(B-(3GdfabGJ GdYGeIs; (3GdejRGfjIs; (3Gdfeh GdOjehZQGajs